2007
DOI: 10.1523/jneurosci.3163-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-1,6-Bisphosphate Has Anticonvulsant Activity in Models of Acute Seizures in Adult Rats

Abstract: A variety of observations suggest that decreasing glycolysis and increasing levels of reduced glutathione, generated by metabolism of glucose through the pentose phosphate pathway, would have an anticonvulsant effect. Because fructose-1,6-bisphosphate (F1,6BP) shifts the metabolism of glucose from glycolysis to the pentose phosphate pathway, it was hypothesized to have anticonvulsant activity. The anticonvulsant activity of F1,6BP was determined in rat models of acute seizures induced by pilocarpine, kainic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 29 publications
8
82
2
3
Order By: Relevance
“…The latency to the first behavioral seizure after pilocarpine administration, referred to as the seizure onset time (SOT), was defined by the occurrence of forelimb clonus, rearing, and loss of balance, and was recorded to the nearest second for each animal by an individual blind to the postnatal treatment of the animal. Seizure onset time is a commonly used measure to describe seizure susceptibility to convulsant compounds in rats (Galic and Persinger, 2005;Lian et al, 2007). Electroencephalographic recordings at the time of overt convulsive behaviors have previously been shown to reveal clear, paroxysmal epileptiform discharges (Cavalheiro et al, 1987;Turski et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…The latency to the first behavioral seizure after pilocarpine administration, referred to as the seizure onset time (SOT), was defined by the occurrence of forelimb clonus, rearing, and loss of balance, and was recorded to the nearest second for each animal by an individual blind to the postnatal treatment of the animal. Seizure onset time is a commonly used measure to describe seizure susceptibility to convulsant compounds in rats (Galic and Persinger, 2005;Lian et al, 2007). Electroencephalographic recordings at the time of overt convulsive behaviors have previously been shown to reveal clear, paroxysmal epileptiform discharges (Cavalheiro et al, 1987;Turski et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…We concluded earlier that the anticonvulsant mechanism(s) of the ketogenic diet in mice may involve a reduction of glucose utilization as fuel. 20 The anticonvulsant actions of 2-deoxyglucose and fructose 1,6-bisphosphate found in animal models [36][37][38] also suggest that reduced glycolysis and/or increased PPP can be anticonvulsant. As trioctanoin appears to alter glucose utilization through glycolysis and the PPP, it is possible that these metabolic alterations are involved in increasing the seizure threshold in naïve mice in this model with trioctanoin but not triheptanoin.…”
Section: Anticonvulsant Effects Of Even Versus Uneven Medium-chainmentioning
confidence: 99%
“…Recently, it has been shown that exogenous administration of FDP can reduce the duration and severity of seizures in laboratory animals (4). In these experiments, the FDP was given into the peritoneal cavity.…”
Section: Introductionmentioning
confidence: 99%